OPTIMALISASI PENDAMPINGAN ORANG TUA TERHADAP KEDISIPLINAN BELAJAR ANAK - Susanti; Eka Danik Prahastiwi (LPPM IAD Probolinggo, 2025)
Parental guidance plays a crucial role in shaping the learning discipline of early childhood. Discipline in early childhood is one of the essential aspects of character and personality development. Children who are disciplined tend to follow rules more easily, take responsibility, and have good self-control. One of the influential factors in children's discipline is the guidance provided by parents. This study aims to analyze the influence of parental guidance on the discipline of early childhood at Pos PAUD Bina Hidayah Kluwih. This study employs a quantitative method with a descriptive approach. Data were collected through observations, interviews, and questionnaires given to parents and educators at Pos PAUD Bina Hidayah Kluwih. The results indicate that children who receive active parental guidance exhibit a higher level of discipline compared to those who receive minimal guidance. Forms of guidance include setting clear rules at home, parents serving as role models, and the consistent application of consequences when children break the rules. Furthermore, effective communication between parents and children also plays a role in helping children understand the importance of discipline. Based on the findings of this study, it can be concluded that parental guidance has a significant influence on the formation of early childhood discipline. Therefore, raising awareness and encouraging active parental participation in guiding children is necessary to instill discipline from an early age. With optimal parental involvement, children can grow into individuals who are more organized, responsible, and possess good self-control. Keywords: Guidance, Parents, Discipline, Early Childhood